The grain boundary pinning effect of the mu phase in an advanced polycrystalline γ/γ′ Co-base superalloy - Freund, Lisa; Stark, Andreas; Pyczak, Florian; Schell, Norbert; Göken, Mathias; Neumeier, Steffen (Journal of Alloys and Compounds, 2018)
A grain boundary pinning phase was introduced into a gamma/gamma' Co-base superalloy by the addition of Mo. The intermetallic phase was identified as mu phase (Co,Ni,Cr)(7)(W,Mo)6 by high-energy X-ray diffraction and energy-dispersive X-ray spectroscopy in the transmission electron microscope. Synchrotron radiation insitu heating experiments confirmed the stability of the grain structure up to 1050 degrees C and therefore the grain boundary pinning effect of this phase. Recrystallization heat treatments at different temperatures resulted in varying amounts of mu phase. The grain size analysis revealed that at least 1% of the phase is necessary to maintain a pinning effect during recrystallization. Atom probe tomography confirmed that Mo partitioned predominantly to the gamma phase. Since the mu phase and the gamma' phase are competing for W, a lower gamma volume fraction was formed in comparison to a Mo-free polycrystalline gamma/gamma' Co-base superalloy variant. However, the homogeneous distribution of small grains resulted in a higher strength compared to the Mo-free alloy without grain boundary pinning phases. The creep resistance at 750 degrees C was similar to the Mo-free alloy as well as the polycrystalline Ni-base superalloy U720Li with a creep rate minimum of 1.5 x 10(-7) s(-1) at 620 MPa. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Co-base superalloys; Grain boundary pinning; Coarsening; Disc alloys; Synchrotron radiation; High-energy x-ray diffraction